Group Roles in Local Food Processing to Achieve Resilience of Agricultural Household Industries in Gunungkidul - Widhiningsih, Diah Fitria; Herliandy, Felisitas Syntia; Raya, Alia Bihrajihant (JSEP (Journal of Social and Agricultural Economics), 2024)
The role of women from small farming families in utilizing surrounding resources to preserve local food is an important issue to study. This study aims to (1) analyze the role of members in groups which include task roles, maintenance roles, and blocking roles, and to (2) analyze the factors influencing group role. This research uses a quantitative descriptive method. Data were collected from 31 respondents selected by the census from the Desa Prima members in Sambirejo, Ngawen, Gunungkidul. Data are analyzed using multiple regression with SPSS. In-depth interviews with group leaders and group member representatives were also conducted to explain cases in roles distribution in Desa Prima. The results showed that task role significantly positively affected the group's enhancement in developing local foods. The group has a clear task distribution so that all works can be completed properly. The role of members as blocking roles is rare and does not have much impact on group dynamics since the members can understand each other. The role of members in how well they can complete the tasks needs to be maintained so that they can still be responsible for completing their tasks properly although some members also have side jobs. Thus, it is necessary to divide the tasks along with a clear timeline. To increase the independence of the home industry, obstacles in the management and processing of local foods should be overcome through increasing the group role.